Introduction to Climate Science - Schmittner, Andreas (Open textbook library., 2018)
This book describes how Earth's climate is changing, how it has been changing in the recent geological past and how it may change in the future. It covers the physical sciences that build the foundations of our current understanding of global climate change such as radiation, Earth's energy balance, the greenhouse effect and the carbon cycle. Both natural and human causes for climate change are discussed. Impacts of climate change on natural and human systems are summarized. Ethical and economical aspects of human-caused climate change and solutions are presented.